Perum Bulog (Logistics Affairs Agency) Medan Regional Office's Public Relations Strategy for Maintaining the Company's Image - Harun Andika; Indira Fatra Deni (LEGAL BRIEF, 2022)
This study aims to describe the public relations strategy of Perum Bulog in the Medan area office in maintaining the company's image. The main purpose of public relations is to make consumers aware of the company and to see the brand/product as trustworthy. Every organization exists in a social, legal, political environment where it has to interact with different institutions and individuals. Public Relations is the process of managing an organization's communications with stakeholders. It plays a company's reputation, compliance, marketing, risk and crisis management. Public relations can include activities built around a favorable corporate image through publicity and public activities (market operations by Bulog). This research is a descriptive qualitative research that aims to explain the public relations strategy of Bulog office in Medan in maintaining the image of the company that is the object of research. The results showed that the Public Relations of Bulog Medan was identified as a tool that really builds the company's image and sustains it because it helps shape the way the organization's public sees or views the organization. This public can be internal or external. The approach adopted by the organization and being proactive is also very important. A proactive approach is better than a reactive approach, because the company may need time to improve its image as a State-Owned Public Company.